Epilepsy in a mouse model of GNB1 encephalopathy arises from altered potassium (GIRK) channel signaling and is alleviated by a GIRK inhibitor - Colombo, Sophie; Reddy, Haritha P.; Petri, Sabrina; Williams, Damian J.; Shalomov, Boris; Dhindsa, Ryan S.; Gelfman, Sahar; Krizay, Daniel; Bera, Amal K.; Yang, Mu; Peng, Yueqing; Makinson, Christopher D.; et al. (Frontiers in Cellular Neuroscience, 2023)
De novo mutations in GNB1, encoding the Gβ1 subunit of G proteins, cause a neurodevelopmental disorder with global developmental delay and epilepsy. Here we show that mice carrying a pathogenic mutation, K78R, recapitulate aspects of the disorder, including developmental delay and generalized seizures. Cultured mutant cortical neurons also display aberrant bursting activity on multi-electrode arrays. Strikingly, the antiepileptic drug, ethosuximide (ETX), restores normal neuronal network behavior in vitro and suppresses SWD in vivo. ETX is a known blocker of T-type voltage-gated Ca2+ channels and G protein-coupled potassium channels (GIRK). Accordingly, we present evidence that K78R results in a gain-of-function (GoF) effect by increasing the activation of GIRK channels in cultured neurons and a heterologous model (Xenopus oocytes) – an effect we show can be potently inhibited by ETX. This work implicates a GoF mechanism for GIRK channels in epilepsy for the first time, identifies a new mechanism of action for ETX in preventing seizures, and establishes this mouse model as a pre-clinical tool for translational research with predicative value for GNB1 Encephalopathy.